(untitled) - Day, Micheal J. (London, 2008)
Univ. of Bristol, UK. Text/reference for students, residents, and practitioners in veterinary medicine. Covers basic immunology, immunotherapy, and immunopathological mechanisms. Details the pathogenesis, diagnosis, therapy, and management of all major immune-mediated diseases of the dog and cat. Includes color and halftone illustrations in a variety of formats.
Keywords: Immunology,Animal deases,Immunity,Miễn dịch học